Building Students’ Career Readiness through Work Readiness: An Analysis of the Influence of Academic Indonesian Language Proficiency and Entrepreneurial Literacy from the Perspective of Social Cognitive Theory - Puspitoningrum, Encil; Muna Almaududi Ausat, Abu; Aqib Shafiq, Muhammad; Suherlan, Suherlan (IJORER : International Journal of Recent Educational Research, 2026)
Objective: This study aims to examine the influence of academic Indonesian language proficiency and entrepreneurial literacy on students’ career readiness, with work readiness tested as a mediating variable. The study focuses on undergraduate students in Malang City, a recognized educational hub in East Java, where students are actively preparing for their future careers. Method: A quantitative research design was employed using survey data collected from 289 undergraduate students across several universities in Malang. Respondents were selected through purposive sampling, requiring them to have completed at least four semesters. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0 to evaluate both direct and mediating effects among the variables. Measurement validity and reliability were confirmed through factor loadings, AVE, Composite Reliability, and Cronbach’s alpha, while structural model significance was tested using bootstrapping. Results: The findings reveal that academic Indonesian language proficiency has a positive and significant effect on career readiness, with work readiness serving as a strong mediator. However, entrepreneurial literacy shows no significant indirect effect on career readiness through work readiness, indicating that entrepreneurial knowledge alone does not sufficiently translate into career preparation without contextual application. Novelty: This study contributes by highlighting the critical role of academic language proficiency often overlooked in employability research as a foundational capability that enhances both work readiness and career readiness, thereby offering new insights for higher education institutions in Indonesia.